Old port location mapping in Kampung Datuk Harun, Pulai Baling Kedah / Mohamad Alif Aiman Mohamad Rosli - Mohamad Rosli, Mohamad Alif Aiman (2021)
Unmanned aerial vehicle (UAV) photogrammetry has shown a very rapid development in many fields, especially in archaeological excavation areas and architectural complexes, where it offers a detailed generation of three-dimensional (3D) data including the possibility of updating over time. It also proves to be a very flexible tool applicable to many types of complex areas with a variety of different features. The use of aerial acquisition provides highly effective results, adding to both rapid capture and lower costs. In fact, today in the field of archaeological research, great efforts are invested in the generation of very large-scale models and orthophoto, and the technology seems to promise further future developments. The aim of the study was to determine the location of an old port near Kampung Datok Harun (Baling region) using aerial photogrammetry data and to display them on modern maps. This study begins with looking the history of Baling area and the study on the surface of the earth in the area using Unmanned Aerial Vehicle (UAV) in providing good data with the available data from Jabatan Ukur Dan Pemetaan Malaysia (JUPEM) which uses conventional photogrammetry method. To accomplish the objective, this software; Agisoft are used to process aerial photographs in the selected area. This study can help the heritage preservation of historical site in Baling, Kedah.